1999
DOI: 10.1159/000006886
|View full text |Cite
|
Sign up to set email alerts
|

The Alcoholic Cardiomyopathies – Genuine and Pseudo

Abstract: Two types of genuine alcoholic cardiomyopathies can produce congestive heart failure, an acute fulminate hyperkinetic type with high cardiac output and a hypokinetic type with a low cardiac output, both of which respond to thiamine. When the chronic alcoholic develops a dilated cardiomyopathy with congestive heart failure without a history of significant malnutrition, then they do not respond to thiamine. This may be explained by a study in which mice given a myotropic virus plus alcohol developed more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Data from our group also suggested that acetaldehyde-induced cardiac mechanical dysfunction may be ablated by folate or thiamine supplementation [Aberle et al 2004[Aberle et al , 2003, suggesting a possible interaction between acetaldehydeinduced cardiac toxicity and nutritional status. This is somewhat consistent with the favorable response of patients with alcoholic cardiomyopathy to thiamine and nutrition treatment [Constant, 1999].…”
Section: Nonacetaldehyde-related Mechanism In Alcoholic Cardiomyopathysupporting
confidence: 81%
“…Data from our group also suggested that acetaldehyde-induced cardiac mechanical dysfunction may be ablated by folate or thiamine supplementation [Aberle et al 2004[Aberle et al , 2003, suggesting a possible interaction between acetaldehydeinduced cardiac toxicity and nutritional status. This is somewhat consistent with the favorable response of patients with alcoholic cardiomyopathy to thiamine and nutrition treatment [Constant, 1999].…”
Section: Nonacetaldehyde-related Mechanism In Alcoholic Cardiomyopathysupporting
confidence: 81%
“…Data from our group also suggested that acetaldehyde-induced cardiac mechanical dysfunction may be ablated by folate or thiamine supplementation [116,117], suggesting a possible interaction between acetaldehyde-induced cardiac toxicity and nutritional status. This is somewhat consistent with the favorable response of patients with alcoholic cardiomyopathy to thiamine and nutrition treatment [118]. …”
Section: Mechanisms Of Alcoholic Diseasessupporting
confidence: 82%
“…In accordance with Bryson`s data (26), alcohol consumption appears to have a more complex relationship with episodes of heart failure, there is no linear dependence. Nonetheless, a strong contribution of hypertension and atrial fi brillation as risk factors for strokes must be considered, especially in the background of heavy drinking (23,27).…”
Section: Discussionmentioning
confidence: 99%